LEARNERS’ STRATEGY FOR TRANSLATING LITERARY TEXT: FIRST-DRAFTING WUTHERING HEIGHTS TRANSLATION ANALYSIS - THOHIRIYAH (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2023)
Literary texts contain complex literary information. Types of literary information are subjective information and objective information. In translating that aforesaid information, there are some obstacles both objective and objective obstacles. Therefore, translating literary works requires proper strategy. This paper examines certain strategies used by the students to render literary information in the process of first-drafting literary text translation. The data in this study are 27 prospective literary pieces of information expressing knowledge about culture, morality, and humanities carried out by the text of Wuthering Heights Chapter 1 by Emily Bronte that has been firstly translated from English to Indonesian by learners joining translation class. The method used in this study is a qualitative one. By adopting the literary translation strategy promoted by Kazakova (2015), the result of this study shows that most students tend to use helper-strategy to compensate for the peculiar information with more neutral equivalent terms in the target language although somehow, they are trapped in unbiased strategy for making the translation product more natural in general.